Behavioral operations: The state of the field - Croson, R.; Schultz, K.; Siemsen, E.; Yeo, M.L. (Journal of Operations Management, 2013)
AbstractThe field of behavioral operations has matured into an established area within the discipline of operations management. The field fills an essential void by laying the micro‐foundations for the broader discipline of operations management. As such, the field examines a variety of topics and is methodologically diverse.